Multidimensional quantum-beat spectroscopy: Towards the complete temporal and spatial resolution of the nuclear dynamics in small molecules - Winter, Martin; Schmidt, Rüdiger; Thumm, Uwe (My University, 2009)
We propose a multidimensional (MD) pump-probe method to image the coupled rovibrational (RV) nuclear dynamics in small molecules. We apply this imaging method to analyze the laser-induced coherent RV nuclear dynamics in D+2 in terms of MD quantum-beat (QB) spectra, without and including an external laser field, by solving the time-dependent Schrödinger equation in full dimensionality. These spectra resolve the internuclear distance R and molecular orientation and reveal (1) the transition frequencies between stationary vibrational and rotational states, (2) their nodal structures, (3) RV couplings, including (4) their influence on the nuclear dynamics on field-free ground state and laser-dressed potential surfaces, and (5) offer an interpretation for an unexplained structure in recently measured QB spectra.